Peranan Sungai Kampar Sebagai Jalur Maritim Perdagangan pada Abad 19 - Hadi Assidiqi; Wan Syahril Fahrezi; Siti Aisah; Nadia Ramona; Ahmal Ahmal (YAYASAN PADHANG MANAH SIBYAN, 2026)
This study aims to examine in depth the role of the Kampar River as a maritime trade route in the 19th century, by tracing the traces of the Minangkabau trade network, traded commodities, and the transportation used. This study uses a library research method, this article explores how the Kampar River, which has a length of 400 km, stretches from the foothills of the Barisan Mountains to the East Coast of Sumatra. The results of this study show that in the 19th century, the Kampar River route was one of the most vital trade routes connecting the interior of Sumatra with the global maritime trade network. Commodities such as gambier, frankincense, resin, and rattan from the Minangkabau interior to international ports in Penang, Singapore, and the Strait of Malacca, the boats used were Kajang boats that could transport commodities in large quantities. Gambier and coffee were the main commodities that had high value in the market. The Kampar River began to be abandoned when the Dutch began building land roads.